The history of small extracellular vesicles and their implication in cancer drug resistance - Palazzolo, Stefano; Canzonieri, Vincenzo; Rizzolio, Flavio (Frontiers in Oncology, 2022)
Small Extracellular vesicles (EVs) in the last 20 years are demonstrated to possess promising properties as potential new drug delivery systems, biomarkers and therapeutic targets. Moreover, EVs are described to be involved in the most important steps of tumor development and progression including drug resistance. The acquired or intrinsic capacity of cancer cells to resist to chemotherapies is one of the greatest obstacles to overcome and improving the prognosis of many patients. EVs are involved in this mechanism by exporting the drugs outside the cells and transferring the drug efflux pumps and miRNAs in recipient cells, in turn inducing drug resistance. In this mini review, the main mechanisms by which EVs are involved in drug resistance are described giving a rapid and clear overview of the field to the readers.